Present temperature field characterization and geothermal resource assessment in the Harbin Area, Northeast China. Issue 2 (March 2019) - Shi, Yizuo; Jiang, Guangzheng; Zhang, Xinyong; Yuan, Zhe; Wang, Zhuting; Qiu, Qianfeng; Hu, Shengbiao
Seven steady-state temperature profiles are logged in the Harbin Area, Northeast China. The temperature data illustrate high conductive thermal gradients with a mean value of 4.78°C/100 m. Temperature maps at depths of 1000, 1500, and 1800 m are represented. The present temperature field is cooling southeastward, with the highest thermal gradients being observed at the junction zone between the Central Depression and the Southeast Uplift of the Songliao Basin. The recoverable heat is calculated using a volumetric method and Monte Carlo simulation. The mean value for recoverable heat from the detailed exploration area around the Harbin Area is 1.052 × 10 19 J (3.59 × 10 11 t standard coal). Geological controls on the present temperature fields are discussed.